Заборона дискримінації за ознаками «гендерна ідентичність» та «сексуальна орієнтація» у світлі теорії прав людини та концепції гідної праці - Амелічева, Лілія Петрівна; Амелічева, Л. П.; Amelicheva, Liliia (ВД "Гельветика", 2020)
У статті висвітлюються правові засади заборони дискримінації за ознаками «гендерна ідентичність» та «сексуальна орієнтація» в суспільно-трудових відносинах. Виявлено проблеми правового забезпечення заборони дискримінації за ознаками гендерної ідентичності і сексуальної орієнтації в трудових відносинах. Так, у національному антидискримінаційному законодавстві не закріплені визначення вказаних «захищених» ознак, не встановлено чіткий правовий механізм протидії дискримінації за цими ознаками в трудових відносинах тощо. Запропоновано в у ст. 6 проекту Закону України «Про працю» № 2708 від 28.12.2019 закріпити дефініції гендерної ідентичності і сексуальної орієнтації.

The article highlights the legal basis for prohibiting discrimination on the grounds of “gender identity” and “sexual orientation” in social and labor relations in the light of the theory of human rights and the concept of decent work. The article is aimed at clarifying the substantive content of the concepts of “gender identity” and “sexual orientation” in the light of the theory of human rights and the concept of decent work, identifying problems of legal support of the prohibition of discrimination on grounds of gender identity and sexual orientation, to develop some proposals for improving anti-discrimination legislation in the field of human rights, in particular in the field of the right to decent work of workers from among persons of the LGBT community. It was found that in the light of the theory of human rights and the concept of decent work, the content of the concepts of “gender identity” and “sexual orientation” is clearly revealed in the Set of legal principles for the application of international human rights law in relation to sexual orientation and gender identity – “Yogyakarta principles”. In the light of the concept of decent work, gender identity and sexual orientation as integral elements of the dignity and personality of each person are also characterized by the fact that they are included in the system of concepts of decent work, since these characteristics should not serve as a basis for discrimination or violations in labor relations. In addition, the prohibition of discrimination on “protected” grounds, in particular on the grounds of gender identity and sexual orientation, is an important dimension or main component of decent work. The problems of legal support for the prohibition of discrimination on the grounds of gender identity and sexual orientation in labor relations are identified. Thus, the national anti-discrimination legislation does not contain definitions of these “protected” features, does not establish a clear legal mechanism for countering discrimination on these grounds in labor relations, and so on. It is proposed in article 6 of the draft law of Ukraine “On labor” No. 2708 of 28.12.2019 to provide definitions of gender identity and sexual orientation. The draft Guidelines for inclusion in collective agreements and agreements of provisions that ensure equal rights and opportunities for women and men in labor relations from 05.07.2019 should clearly identify typical situations of discrimination on these grounds and develop an algorithm for the actions of the employee – victim of discrimination and the employer in such situations.
Амелічева, Л. П. Заборона дискримінації за ознаками «гендерна ідентичність» та «сексуальна орієнтація» у світлі теорії прав людини та концепції гідної праці / Л. П. Амелічева // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 70-76.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; дискримінація за «захищеними» ознаками; вимір гідної праці; Джокьякартські принципи; сексизм; discrimination based on “protected” characteristics; measurement of decent work; the Yogyakarta principles; sexism